Aroma encapsulation for eco-friendly textile application - Sharkawy, Asma (AUC Knowledge Fountain, 2016)
The textile industry sector has shown a growing interest in the functionalization of conventional fabrics to produce innovative products that enhance health, safety and ergonomics. This research is concerned with developing a functional fabric with durable antibacterial and fragrant properties by employing green chemistry materials and processes. This was achieved by microencapsulation of aroma compounds in biodegradable polymers by the complex coacervation method. Afterwards, the produced microcapsules were covalently attached to cotton fabrics by means of thermofixation grafting process using a polycarboxylic acid. The effects of different processing parameters, including the type and amount of the emulsifier, the type and amount of the hardening agent, and the wall to core ratio, on the morphology, size, dispersion, encapsulation efficiencies (EE%) of the produced microcapsules were examined. The release profiles of the active agents were investigated. The impact of different grafting conditions on the microcapsules adhesion was inspected. Scanning electron microscopy (SEM) and Fourier Transform Infrared (FTIR) spectroscopy confirmed the adhesion of the produced microcapsules on the cotton fabrics. The antibacterial assays of both the produced microcapsules and the functionalized fabrics demonstrated that they exhibited a sustained antibacterial activity.